Characterization of BaMoO4, BaWO4, CaWO4 and CaMoO4 compounds obtained by polymeric precursor method and by microwave-assisted hydrothermal method - Alencar, Lorena Dariane da Silva (2018)
Molybdates and tungstates belonging to the scheelite family constitute an important class of materials, which have advantages as a relatively low cost and being non-polluting. Barium molybdate (BaMoO4), barium tungstate (BaWO4), calcium molybdate (CaMoO4) and calcium tungstate (CaWO4) have been extensively studied due their photoluminescent properties, besides that they also present catalysis and photocatalysis applications. However, to the best of our knowledge there are no structural characterizations of BaMoO4, BaWO4 and CaMoO4 by x-ray absorption spectroscopy (XAS) in the literature. In this work, powders of these 4 compounds were prepared by microwave-assisted hydrothermal (MAH) method and polymeric precursor method (PPM) and their structural properties were characterized by X-ray diffraction (XRD), X-ray absorption near edge spectroscopy (XANES) and extended X-ray absorption fine structure (EXAFS) measurements. The morphology and particle size of these crystalline powders were observed by field emission scanning electron microscopy (FE-SEM). Furthermore, BaMoO4, BaWO4 and CaWO4 were employed as solid catalysts towards gas phase toluene oxidation reactions and their optical properties were investigated by ultraviolet visible (UV-Vis) absorption and photoluminescence (PL) measurements. XRD patterns confirm the phase purity of materials from both preparation methods and reveal a preferential growth when the powders are prepared by MAH due polymeric agents and processing using microwave, which was confirmed by FE-SEM. XANES and EXAFS results show that the preparation method did not introduce high disorders into the structure, however the H2 Temperature-Programmed Reduction (H2-TPR) measurements indicated that the catalyst reducibility is affected by the preparation method of the samples. PL emissions were attributed to the charge-transfer transitions within the [WO4]2- and [MoO4]2- complexes.